Göttingen in Baltimore or the Americanization of the German University? - Robert D. Reisz (University Babes-Bolyai, 2018)
The paper intends to reconstruct the conceptual origins of the Humboldtian model and follow the way these were imported to the United States. After introducing the basic concepts of the Humboldtian reforms, as these were defined by Kant, Fichte and Humboldt, we analyze the fundamental concepts of Daniel Coit Gilman, the first rector of Johns Hopkins University. The differences between the "German" university and the "American" research university are discussed as conclusions to this analysis.